Combining mesoscale thermal transport and x-ray diffraction measurements to characterize early-stage evolution of irradiation-induced defects in ceramics. (July 2020) - Khafizov, Marat; Riyad, M Faisal; Wang, Yuzhou; Pakarinen, Janne; He, Lingfeng; Yao, Tiankai; El-Azab, Anter; Hurley, David
Abstract: In situ characterization of defects, microstructure, and properties will provide new perspectives regarding the structure-property relationship of materials in extreme environments. In this communication, we investigate the utility of laser-based thermal transport measurements in combination with X-ray diffraction as a means to characterize the early-stage evolution of irradiation-induced defects in ceramics. Uranium dioxide is used as a model system to analyze the impact of irradiation-induced defects with 2.6 MeV H and 3.9 MeV He ions up to a dose of 0.1 displacement per atom (dpa) at low temperature. For these radiation regimes, the formation of extended defects such as loops and voids is limited as compared to point defects. Lattice expansion was determined from X-ray diffraction analysis. Modulated thermoreflectance was used to measure the thermal conductivity of the ion damaged region. Both H and He irradiation leads to an expansion of the crystal lattice and a reduction in thermal conductivity. For the same dpa, the lattice expansion and conductivity reduction were notably different for H and He irradiated samples. The results were analyzed using simple models for lattice expansion and thermal conductivity reduction, informed by atomistic simulation from the literature. The modeling results suggest that the difference in the defect kinetics between two conditions can be attributed to ionization induced enhanced defect mobility and the stability of Schottky defects. These results demonstrate the utility of thermal conductivity measurements as a tool for characterization of microstructure under irradiation. Graphical abstract: Image, graphical abstract